DIRECTIVE ILLOCUTIONARY ACTS IN JAPANESE TEEN MOVIES PEACH GIRL AND MISEINEN DAKEDO KODOMO JANAI - Ghaisani Adnjani CH; Mulyadi; Diah Syafitri Handayani (Leksema: Jurnal Bahasa dan Sastra, 2023)
This study aimed to describe the meaning of directive illocutionary speech acts in two Japanese movies entitled Peach Girl and Miseinen Dakedo Kodomo Janai. The directive illocutionary act is the most frequently used speech act in everyday life. In Japanese language, the meanings of these speech acts are often misinterpreted by Japanese language learners, so that the meanings of the speeches are not conveyed properly. In the movies Peach Girl and Miseinen Dakedo Kodomo Janai, the characters use a lot of directive illocutionary speech acts. Therefore, it is worth to conduct a deeper study regarding the meaning of those directive speech acts. This research used speech act theory proposed by Searle (1979) and applied descriptive-qualitative method. The results show that there are 10 meanings of directive illocutionary speech acts with their own structural characteristics, namely command (used in polite language form) order (with V~te form), beg (with the word onegai), request (with V~te form), invitation (with invitation form V~ou), deny (with ~nai form), advise (with V~nda form), prohibition (with V~nai form), warn (with V~te form and particle ~ne), and ask (with keigo form).